Evaluasi Kebijakan Internasionalisasi Universitas Brawijaya dalam Rangka Menuju World Class University - Khadafi, Muamar; Hariyono, Bambang Santoso; Wanto, Alfi Haris (Jurnal Ilmiah Administrasi Publik, 2018)
University role in supporting internationalization is considered necessary to be implemented because the issue of internationalization is one of the impact of globalization, not only in the field of information technology but also in education. Brawijaya University has committed to become a world-class university through its policies to support the goal of Universitas Brawijaya become World Class University. To reach that stage, the internationalization policy adopted by UB must be truly targeted. The results of the research indicate that the assessment of the implementation of UB's internationalization policy in terms of inputs, processes and outputs indicates the inefficiency of the implementation of the policy because it has not balanced the input, process, and the results obtained, while several obstacles found in the process of Internationalisation.